Situational Analysis: Community Care for Survivors of Stroke and Suggestions for Improving the Provision of Care - Yaowapanon, Nootchayong; Buddhirakkul, Prapim; Srisuphan, Wichit; Senaratana, Wilawan; Potempa, Kathleen; Chontawan, Ratanawadee (Pacific Rim International Journal of Nursing Research, 2018)
This descriptive qualitative study aimed to analyze the community care situation for survivors of stroke and provide suggestions for improving care. The study was conducted in a district of Chiang Mai Province. Purposive sampling was employed based on inclusion criteria to select 51 key informants comprised of 1) three health personnel, 2) 13 community leaders, 3) three local government officers, 4) 13 village health volunteers, and 5) 13 caregivers who took care of survivors of stroke. The data collection consisted of in-depth interviews and focus group discussions, based on the Expanded Chronic Care Model. Data were analyzed by content analysis. The results revealed that community care for survivors of stroke is mainly provided by family members. As well, our analysis revealed for survivors: 1) inadequate personal skills among caregivers and volunteers; 2) inefficient health services; 3) the lack of support for a caring system; 4) incomplete clinical information system; 5) no healthy public policy; and 6) lack of a supportive environment. We suggest that, to improve the care available to survivors of stroke, there needs to be: 1) development of supportive policies at both national and local government levels; 2) development and provision of guidelines for the care; and 3) a supportive caring system that includes health personnel, caregivers, and rehabilitation facilities, as well as support for the home and community-based environment. These results and suggestions will be useful to community nurses and stakeholders who are responsible to design caring for survivors of stroke.